Лексико-семантична група якісних прикметників у творчості поетів Нью-Йоркської групи - Осипчук, В. М. (My University, 2017)
У статті розглядаються особливості номінації поетичного текс- ту в естетиці модерну (на матеріалі поетів Нью-Йоркської групи) із залученням значеннєвого потенціалу лексико-семантичної групи якісних прикметників. Категорія якості розглядається як філософ- ська константа, атрибут, що має власну специфіку репрезентації у мові.
The articie discusses the features of the category of the poetic text in the aesthetics of modernity (based on the poets of the new York group) with the assistance of the semantic potential of lexical-semantic group of qualitative adjectives. The quality is regarded as a philosophical constant, the attribute having its own specificity of representatbn in language. The lexico-semantic group of qualitative adjectives and pragmatic guidelines for their use in poetic texts is a phenomenon whose consideratbn has particularly recently attracted the attention of researchers. The lexicosemantic group of qualitative adjectives clearly defines the category of quality in the poetic text, which generates the semantb richness and originality of the modem-day poetry of the New York group of poets.
Keywords: прикметник; семантика; ступені порівняння; adjective; semantics; degree of comparison